Correction: Folate-decorated polymeric Pt(ii) prodrug micelles for targeted intracellular delivery and cytosolic glutathione-triggered release of platinum anticancer drugs. Issue 15 (11th March 2015) - Jamal Tabatabaei Rezaei, Seyed; Amani, Vahid; Reza Nabid, Mohammad; Safari, Nasser; Niknejad, Hassan; Notash, Behrouz
Abstract : Correction for 'Folate-decorated polymeric Pt(ii ) prodrug micelles for targeted intracellular delivery and cytosolic glutathione-triggered release of platinum anticancer drugs' by Seyed Jamal Tabatabaei Rezaei et al ., Polym. Chem., 2015, DOI: 10.1039/c5py00156k.